Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1361-6501/ac8440
|View full text |Cite
|
Sign up to set email alerts
|

A game theory enhanced domain adaptation network for mechanical fault diagnosis

Abstract: Transfer learning (TL) technology have been successfully applied to address the domain adaptation (DA) problem in machinery fault diagnosis. However, partial DA problem is more suitable for industrial applications, where the target data only covers a subset of the source classes, which makes it difficult to know where to transfer the target data. To overcome this problem, a novel game theory enhanced domain adaptation network (GT-DAN) is proposed in this paper. Based on different metrics, including Maximum mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, it requires monitoring of the equipment operation and collecting valid failure data or performance degradation data. Data-driven approaches generally include those based on statistically driven models and reliability functions, as well as those based on machine learning and deep learning models are the main directions of current life prediction research [11][12][13][14]. For rolling bearings, the main prediction steps include: (1) extracting failure characteristics and degradation curves using signal processing or machine learning; (2) constructing health indicators using deep learning or degradation function models to characterize life thresholds; (3) using the trained deep learning degradation models for life prediction or model fitting the obtained degradation curves to finally obtain the RUL [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires monitoring of the equipment operation and collecting valid failure data or performance degradation data. Data-driven approaches generally include those based on statistically driven models and reliability functions, as well as those based on machine learning and deep learning models are the main directions of current life prediction research [11][12][13][14]. For rolling bearings, the main prediction steps include: (1) extracting failure characteristics and degradation curves using signal processing or machine learning; (2) constructing health indicators using deep learning or degradation function models to characterize life thresholds; (3) using the trained deep learning degradation models for life prediction or model fitting the obtained degradation curves to finally obtain the RUL [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 10 ] proposed a class-weighted adversarial neural network that encourages positive transfers of shared classes and ignores source class outliers through class-weighting strategies. Sun et al [ 11 ] suggested a game theory-enhanced domain adaptation network to solve partial domain adaptation problems. The network constructs three attention matrices using maximum mean discrepancy, Jensen-Shannon divergence, and Wasserstein distance and generates the best probability weight through the combination of game theory weights, thereby filtering out irrelevant source domain samples and improving mechanical fault diagnosis performance.…”
Section: Introductionmentioning
confidence: 99%